Sensation™ Brand ‘Florida127’ Strawberry - Vance M. Whitaker; Craig K. Chandler; Natalia A. Peres (EDIS)
‘Florida127′ is a new strawberry cultivar released from the University of Florida in 2013, the fruit of which are eligible for marketing under the Sensation™ brand. It is a short-day plant adapted to annual, winter plasticulture growing systems. The plant is moderately compact, robust, and upright with long pedicels, making the fruit easy to harvest. This 4-page fact sheet provides information and recommendations based on several years of testing in field plots in west-central Florida. Comparisons are made to ‘Florida Radiance’ and ‘Strawberry Festival’ for disease resistance. Written by Vance M. Whitaker, Craig K. Chandler, and Natalia A. Peres, and published by the UF Department of Horticultural Sciences, October 2014. (Photo by Vance M. Whitaker)